Evolving hematopoietic stem cell transplantation strategies in severe aplastic anemia. Issue 1 (February 2016) - Dietz, Andrew C.; Lucchini, Giovanna; Samarasinghe, Sujith; Pulsipher, Michael A.
Abstract : Purpose of review: Significant improvements in unrelated donor hematopoietic stem cell transplantation (HSCT) in recent years have solidified its therapeutic role in severe aplastic anemia (SAA) and led to the evolution of treatment algorithms, particularly for children. Recent findings: Advances in understanding the genetics of inherited bone marrow failure syndromes (IBMFS) have allowed more confidence in accurately diagnosing SAA and avoiding treatments that could be dangerous and ineffective in individuals with IBMFS, which can be diagnosed in 10–20% of children presenting with a picture of SAA. Additionally long-term survival after matched sibling donor and matched unrelated donor HSCT now exceed 90% in children. Late effects after HSCT for SAA are minimal with current strategies, and compare favorably to late effects after upfront immunosuppressive therapy, except for patients with chronic graft versus host disease. Summary: Careful assessment for signs or symptoms of IBMFS, along with genetic screening for these disorders, is of major importance. Matched sibling donor HSCT is already considered the standard of care for upfront therapy and some groups are evaluating matched unrelated donor HSCT as primary therapy. Ongoing studies will continue to challenge treatment algorithms and may lead to an even more expanded role for HSCT in SAA.